2022
DOI: 10.3390/su142113921
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Purchase Intention on Agricultural Products via Public-Interest Live Streaming for Farmers during COVID-19 Pandemic

Abstract: In order to sell unmarketable products and alleviate farmers’ economic difficulties caused by the COVID-19 pandemic, public-interest livestreaming for farmers with the property of altruism has been emerging as a new way of mobile commerce and has attracted a huge amount of attention among Chinese consumers. In this paper, based on the theory of reasoned action, we intend to explore the influencing factors from the levels of the platform, product, and consumer that affect consumers’ attitudes and purchase inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…According to Roseira's study [30] , the higher level of purchase intention that consumers generate, the more possibility that consumers will make an actual purchase. Thus, purchase intention is deemed the most critical step for the food industry [2] . The first antecedent is the personal attitude, a willingness generated from past experience that influences a person's response to a particular object or situation [27,31] .…”
Section: Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
See 3 more Smart Citations
“…According to Roseira's study [30] , the higher level of purchase intention that consumers generate, the more possibility that consumers will make an actual purchase. Thus, purchase intention is deemed the most critical step for the food industry [2] . The first antecedent is the personal attitude, a willingness generated from past experience that influences a person's response to a particular object or situation [27,31] .…”
Section: Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
“…Agricultural products refer to "any agricultural commodity or product, whether raw or processed, including any commodity or product derived from livestock for human or livestock consumption" [1] . Generally, fresh products like vegetables and fruits are easily perishable [2] . In this case, an effective agricultural product supply chain is critical.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interaction is a crucial aspect of live-streaming commerce (Kang et al, 2021), and it significantly influences consumers' purchasing decisions during live-streaming events. Among recent relevant studies, Dong et al (2022) and Yu and Zhang (2022) have shown that live interaction can positively affect consumers' purchasing decisions for agricultural products. However, current research has not addressed how to interact to improve consumers' purchasing decisions for agricultural products, which is essential for practitioners to address the practical challenge of low audience engagement or lack of orders in live sessions.…”
Section: Introductionmentioning
confidence: 99%